1993
DOI: 10.1002/ijc.2910550105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of a tumor‐cell‐derived collagenase‐stimulatory factor in urothelial carcinoma: Its usefulness as a tumor marker for bladder cancers

Abstract: A mouse monoclonal antibody (MAb) E11F4, previously raised against the tumor-cell-derived collagenase-stimulatory factor (TCSF) from LX-1 human lung-carcinoma cells, has been used to define the expression and distribution of TCSF in human non-neoplastic urothelium and tumors of the urinary bladder. Immunohistochemically, TCSF was detected in 27/28 transitional-cell carcinomas (TCC) of the bladder, of which 23 were judged to be positive for TCSF according to objective criteria. Twenty-four of 28 non-neoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 18 publications
3
65
0
Order By: Relevance
“…4 CD147 is more highly expressed on the surface of most human carcinoma cells compared to their normal counterparts and correlates with tumor progression and invasion by stimulating peritumoral fibroblasts to produce elevated levels of several MMPs. 4,[11][12][13][14][15][16] These results imply that a CD147 counterreceptor might exist on the surface of fibroblasts, but none has been identified. Using CD147-transfected COS cells and immobilized recombinant CD147-Fc fusion protein, it was revealed that CD147 engages in a homophilic interaction, providing evidence that CD147 may be a counterreceptor for itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 CD147 is more highly expressed on the surface of most human carcinoma cells compared to their normal counterparts and correlates with tumor progression and invasion by stimulating peritumoral fibroblasts to produce elevated levels of several MMPs. 4,[11][12][13][14][15][16] These results imply that a CD147 counterreceptor might exist on the surface of fibroblasts, but none has been identified. Using CD147-transfected COS cells and immobilized recombinant CD147-Fc fusion protein, it was revealed that CD147 engages in a homophilic interaction, providing evidence that CD147 may be a counterreceptor for itself.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Expression of EMMPRIN is enhanced in a variety of human carcinomas and correlates with tumor progression and invasion by inducing production of MMPs by stromal cells. 4,[11][12][13][14][15][16] It was also shown in vitro that recombinant EMMPRIN purified from Chinese hamster ovary cells transfected with cDNA for human EMMPRIN stimulates cultured human fibroblasts to produce MMP-1, MMP-2 and MMP-3. 17 EMMPRIN not only stimulates the production of interstitial collagenase (MMP-1) but also forms a complex with MMP-1 at the human lung carcinoma cell surface, which would facilitate invasive processes.…”
Section: Abstract: Basigin (Cd147); Malignant Melanoma; Invasion; Mementioning
confidence: 99%
“…EMMPRIN expression was found in the synovial fibroblast-like cells and granulocytes, but not in the infiltrating lymphocytes or macrophage-like cells. In tumors, EMMPRIN has been detected on the surface of tumor cells, but not on adjacent fibroblasts (15)(16)(17). In RA, however, fibroblast-like synovial cells are the primary cells that express EMMPRIN.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 expression is elevated on several human tumors and has been correlated with the malignancy in some cancers such as primary breast cancer and ovarian cancer, etc. (7)(8)(9)(10)(11)(12). Despite the close correlation between CD147 expression and malignancy of some tumors, it is not clear whether CD147 has a functional role in tumor genesis and hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%